Real-life LDL-C treatment goals achievement in patients with heterozygous familial hypercholesterolemia in the Czech Republic and Slovakia: Results of the PLANET registry. (October 2018) - Vrablik, Michal; Raslová, Katarina; Vohnout, Branislav; Blaha, Vladimir; Satny, Martin; Kyselak, Ondrej; Vaclova, Martina; Urbanek, Robin; Maskova, Jana; Soska, Vladimir; Freiberger, Tomas
Abstract: Background and aims: Despite the high prevalence of familial hypercholesterolemia (FH) and available effective lipid-lowering therapy, most of the individuals with this disorder remain undiagnosed and undertreated. The aim of the PLANET registry was to assess the real-life attainment of low-density lipoprotein cholesterol (LDL-C) therapeutic target level in patients with heterozygous FH, to characterize prescribed lipid-lowering therapy with assessment of its efficiency according to the attainment of the target LDL-C level, and to characterize cardiovascular events observed in this patient population again in relation to LDL-C target level attainment. Methods: PLANET registry was designed as a non-interventional, retrospective, cross-sectional, multicentre disease registry for adult patients with heterozygous FH in the Czech Republic and Slovakia. Results: Overall, 1755 patients were enrolled at 32 sites specialized in FH treatment. 15.4% of patients attained the target LDL-C value. The proportion of patients with LDL-C goal achievement increased to 17.3% in the subgroup of patients receiving high-intensity statin therapy (54.6% of study population). Out of 55 patients receiving inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9), 61.8% reached the LDL-C treatment goal. Of all cardiovascular events reported, 14.0% occurred in patients attaining the LDL-C goal, while it was 86.0% in the not-at-target group. It was documented ( p =0.004) that the longer is the patient in care at the specialized FH centre, the higher is the probability that he/she will attain the target LDL-C level. Conclusions: Although target LDL-C level attainment remains relatively low, the likelihood of LDL-C goal attainment increases with duration of specialized care. Highlights: 15.4% of patients with heterozygous FH achieved LDL-C goal attainment High intensity lipid-lowering therapy was used by 54.6% patients The longer the care by a specialist, the higher the probability of LDL-C goal attainment